Economic importance of cultural industry in South Korea - Hajduková, Zuzana (2022)
The aim of this bachelor thesis is to get introduced into the complexity of cultural and creative content industries as well as this new socio-economical cultural phenomenon of Korean Wave and measure its effect on South Korea. Cultural industries are characterized by a number of classifications which differ not only on the basis of countries but even of organizations. The South Korean cultural industry has become an important part of the country’s economy over the last 20 years, and despite its size, it has managed to develop into the seventh largest exporter of cultural content in the world. Overall, this sector affects the entire economy of the country, its image, nation’s brand, diplomatic relations, and tourism. Ultimately, this work explains the important interconnection of the cultural industries with other sectors that interact together. These interconnected relationships then continue to operate and spread in areas such as language learning or the spread of Korean culture around the world.